2019
DOI: 10.1038/s41598-019-49479-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Validation of Reference Genes for Quantitative Real-Time PCR in Helopeltis theivora Waterhouse (Hemiptera: Miridae)

Abstract: Helopeltis theivora Waterhouse is a predominant sucking pest in many tropic economic crops, such as tea, cocoa and coffee. Quantitative real-time PCR (qRT-PCR) is one of the most powerful tools to analyze the gene expression level and investigate the mechanism of insect physiology at transcriptional level. Gene expression studies utilizing qRT-PCR have been applied to numerous insects so far. However, no universal reference genes could be used for H. theivora. To obtain accurate and reliable normalized data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
(69 reference statements)
4
17
0
Order By: Relevance
“…Consistent with observations in previous studies 7 , 12 , 13 , the three algorithms, NormFinder, BestKeeper and geNorm, produced different results when ranking gene stability in the present study; therefore, the combined use of all algorithms would ensure more credible results 13 . Considering the cutoff values in each algorithm, most of the seven candidate genes could be deemed acceptable for use as reference genes when analysing gene expression in different conditions in honey bees.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with observations in previous studies 7 , 12 , 13 , the three algorithms, NormFinder, BestKeeper and geNorm, produced different results when ranking gene stability in the present study; therefore, the combined use of all algorithms would ensure more credible results 13 . Considering the cutoff values in each algorithm, most of the seven candidate genes could be deemed acceptable for use as reference genes when analysing gene expression in different conditions in honey bees.…”
Section: Discussionsupporting
confidence: 90%
“…Given the importance of accurate normalisation in qRT-PCR assays, reference genes have been identified and validated in various insect species 8,13,14 . According to previous studies of the honey bee, widely used reference genes were validated at different developmental stages 6 , in the brains after a bacterial challenge 15 , different ages and social roles 7,10,16 .…”
mentioning
confidence: 99%
“…However, gapdh and rps 18 were suggested to be the optimal reference genes for RT-qPCR-based under the labor-specific gene expression, bacterial infected and developmental gene expression in Western honey bee as shown in Table 2 ( Scharlaken et al, 2008 ; Reim et al, 2013 ; Moon et al, 2018a ). Previous studies have shown that some ribosome-associated genes have been used as stable internal reference genes for quantitative analysis ( Wang et al, 2019 ). For instance, Freitas et al (2019) found that rpl 32, rps 5, and rps 18 were identified as suitable reference genes for the different tissues of stingless bees.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the gene expression patterns across different experimental or biological conditions can provide valuable insights into the regulation of the metabolic pathways that help cells withstand or adapt to environmental change. In this context, RT-qPCR is one of the most commonly used approaches to measure gene expression levels owing to its accuracy, sensitivity, specificity, precision, real-time detection of the reaction progress, dynamic range, and the speed of analysis [ 19 22 ]. However, a range of factors can significantly diminish the accuracy and reliability of RT-qPCR data, such as quality and quantity of the mRNA templates, enzymatic efficiency of the reverse transcription and PCR amplification reaction, and differences between cells or tissues in the overall transcriptional activity and mRNA half-life [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several statistical algorithms have been developed to identify the most suitable reference genes under a given set of experimental or biological conditions in order to avoid artifacts due to normalization, and include geNorm [ 27 ], NormFinder [ 28 ], BestKeeper [ 29 ], the comparative Δ C T method [ 30 ], and the web-based program RefFinder [ 31 ]. These tools have been carried out on a broad range of species, including whole organisms, specific tissues or cell types from animals [ 19 21 , 32 , 33 ], plants [ 34 37 ], and fungi [ 38 , 39 ]. Selection of reference genes has also been addressed in macroalgae [ 40 42 ] as well as in specific microalgae species, including the diatoms Phaeodactylum tricornutum [ 43 ], Pseudo-nitzschia multristrata and P .…”
Section: Introductionmentioning
confidence: 99%